# Proofathon Algebra Solutions

Cody Johnson
24 January 2014 – 2 February 2014
1. Solve for x if x((x − 3)x + 2017) = 2.
Solution (by Ahaan Rungta).
x((x − 3)x + 2017) = 2 =⇒ x3 − 3x2 + 2017x − 2 = 0
Now, we use the Cubic Formula to find one of the roots. It states that if  

b 3 bc − 3ad c
(p, q, r) = − , p +
,
,
3a
6a2
3a
then

r
x=

3

q
q+

r
q2

+ (r −

3
p2 )

+

3

q−

q

3

q 2 + (r − p2 )

is a root. Note that, here, we have a = 1, b = −3, c = 2017, and d = −2. Substituting this truckload,
we get that
s
r 

2
1  √
3
3
√ 
+
x = 1 − 2014 ·
· 13 582002193 − 18117
18
3 · 13 582002193 − 18117
is a root. If we let this be v, then divide the original cubic by x − v to get a quadratic. The solutions
s 

√ 
2
√ 

x = 1 + 1007 · 1 ± i 3 · 3
3 · 13 582002193 − 18117

√ ! r 

1  √
1∓i 3
3
·
· 13 582002193 − 18117 ,
2
18

and we are done.
2. Let m, n, k be three positive reals, and let b = 

m2 + k 2 , a =

n2 + k 2 . If 

2  
2  

bn
am
1
1
+m −
+ n = (m + n)2 k 2

,
b+m+n
a+m+n
(a + m + n)2
(b + m + n)2

show that m = n.
Solution. Consider a triangle 4ABC with coordinates A(0, k), B(−m, 0), and C(n, 0). Let the
internal angle bisector of ∠B and ∠C meet CA and BA at D and E, respectively. Since BC = m + n,
BA = b, and CA = a, we have

1

  bn (m + n)k D= . Hence. 3. i=1. . . . 2014}. . Solution. f (n) (x) = x has 9n distinct real solutions x. Rewrite as f (x) = x(4x2 −3)(4(x(4x2 −3))2 −3). But from here. 3. . 2014} → R satisfies the following relation: 2014 X f (i)f (j) = 1 for j = 1. . for any m ∈ {1. BA = CA. Prove that for all | {z } n times positive integers n. Solution (by Ahaan Rungta). We get: 2 2 S · f (m) − [f (m)] = 1 =⇒ [f (m)] − S · f (m) + 1 = 0. we have  2  2  2  2 bn (m + n)k bn (m + n)k +m + = +n + m+n+b m+n+b m+n+b m+n+a which is equivalent to the condition that BD = CE. But. f (m) This is a quadratic. 2014. 2. . 2014 X ∀j ∈ {1. or a = b. such that m = n. This is clearly g(g(x)) for g(x) = x(4x2 −3). . has only 9n solutions in total. Then. i=1. 2 . (x) . 2.i6=j Let S = 2014 X f (i). sin n − 1 . )). Hence. sin n − } 9 2 9 2 9 2 9 2 Since the Fundamental Theorem of Algebra states that a polynomial of degree 9n . . which f (n) (x) clearly is. 2. . m+n+b m+n+b   an (m + n)k E= . . sin n {sin n − . From the given conditions. · · · . (b) Find a closed form for f . · · · . A simple inductive argument shows that f (n) (sin θ) = sin 9n θ. so f (m) = S± 2 √ S2 − 4 . . 2. Let f (x) = x(4x2 − 3)(64x6 − 96x4 + 36x2 − 3) and f (n) (x) = f (f (. . so we’re done. 4. it’s easy to see that sin 9n θ = 0 has solutions for 9n distinct values of sin θ because consider    n  n    π 9n π 9n π 9 π 9 + 1 . A function f : {1. 2014} f (i)f (j) = 1.i6=j (a) Find the period of f . we can deduce that f (sin θ) = sin(3(3θ)) = sin 9θ. from the Steiner Lehmus theorem. . where we can solve for f (m). m+n+a m+n+a as a consequence of the angle bisector theorem. it is easy to note that. this reminds us of the identity g(sin θ) = sin θ(4 sin2 θ − 3) = sin 3θ. . . we have i=1 S − f (m) = 1 . these values of sin θ are our roots. 3.

for all m. 2. we have 1007 − p S p − 1007 =√ > 1 =⇒ p > 2013. S2 − 4 pS (2014 − p) · S p· = + + 2 2 =⇒ S s− √ S 2 − 4. If. S= 2014 X f (i) i=1 =p· S+ s+ √ s2 + 4 2 ! + (2014 − p) · = = =⇒ 1006S 1007 − p =⇒ 1006 = = If S is positive. Then. on the other hand. 2 so we can solve for S. · · · . we have 1007 − p > 1 =⇒ p < 1. note that. we get that √ S − S2 − 4 f (m) = . ∀m ∈ {1. 2014}. Thus.√ √ S2 − 4 S − S2 − 4 . 2014 2013 3 . S is negative. Let there 2 2 be p occasions of the former (plus) and thus 2014 − p of the latter. since S > √ √ s2 + 4 2 ! √ S 2 − 4 (2014 − p) · S 2 − 4 − . 10062 S 2 2014 · f (m)   p = 1007 · S − S 2 − 4 p = 1007S − 1007 S 2 − 4 p = 1007S − 1007 S 2 − 4 p = 1007 S 2 − 4  = 10072 · S 2 − 4  = 10072 · S 2 − 4  = 10072 · S 2 − 4 10062 S 2 = S S S S 1006S 10062 S 2 10062 S 2 = 10072 S 2 − 20142 20142 20142 S2 = = 10072 − 10062 2013 2014 S = √ 2013 √ S 2013 =⇒ f (m) = = . or . 2 2 √ pS pS p · S2 − 4 + 1007S − + 2 2 √ 2 p p · S2 − 4 −1007 · S 2 − 4 + 2 p p 2 −1007 · S − 4 + 1007S + p · S 2 − 4 p (1007 − p) · S 2 − 4 S √ . the function f takes on one of two values. In the former case. =⇒ 2 1006 1006 S −4 so p = 2014. 1006 so p = 0.

Plugging this into the latter equation. for all i in the domain. 2014 2014 and we get |S| = √ . and 8 be written on a blackboard. 2. so S = − √ . where p = 2014. (b) The closed form of f could take on two values: √ f (i) = ± 2013 . Hence. m + n ≥ a + b. We recall that S is negative. 6. Find all triples of real numbers (x. 2. implying that 2013 2013 √ 2013 f (m) = − . · · · . z) such that (x2 − y 2 )2 + (y 2 − z 2 )2 + (z 2 − x2 )2 = 4xyz(x + y + z) − 8xz 2 (x + y) Solution. · · · . 2013 5. n that satisfies mn = ab. Thus. y. This can be rewritten exclusively in terms of sin θ to find 0 = sin4 θ − 2 sin3 θ + sin2 θ + 2 sin θ − 1 4 3 2 Hence. the solution to the equation is 2 (x. z) = (ct. we have √ S + S2 − 4 . Every second. b written on the board by two positive real numbers m. ±c 1 − t ) for some real c. Cody can either (a) Add any positive real number to any positive real number written on the board. The former implies the substitution of x = y cos θ and z = y sin θ for some θ. 2013 and we are done. 2014}. In the latter case. we get cos θ = sin θ + sin θ cos θ.for all i. implying that each term is equal to 0. 4 . so 1006 · |S| = 1007 · p |S|2 − 4. (b) Replace any two positive real numbers a. ∀m ∈ {1. 6. c. y. f (m) = 2 ∀m ∈ {1. x2 + z 2 = y 2 and xy = yz + zx. Let the numbers 1. for each real √ t that is a root of 0 = t − 2t + t + 2t − 1. Following a similar approach as before. we obtain S = 1007S + 1007S · p S 2 − 4. 2014}. Expand out the equation and rewrite as (x2 − y 2 + z 2 )2 + (−xy + yz + zx)2 = 0 This is an equality case of (x2 − y 2 + z 2 )2 + (−xy + yz + zx)2 ≥ 0. since it is a constant. 7. our answers are: (a) The period of f is 1 .

is greater than the coded sum of {2. 3. 3. b. z) of positive reals such that ( (x + y + z)(x3 + y 3 + z 3 + xyz) = 2014 + x2 (x2 − y 2 ) + y 2 (y 2 − z 2 ) + z 2 (z 2 − x2 ) √ √ √ 2xyz( xy + yz + zx) = 1007 Solution. for the set of numbers {a} on the board. fn (x) = P (fn−1 (x) + 1) − 4 2f2014 (x)+8 1 Prove that the triplet {a. 4. 161. we get √ (x2 + yz)(y 2 + zx) = x2 y 2 − z 4 + z(x3 + y 3 + z 3 ) ≥ 4xyz xy √ (y 2 + zx)(z 2 + xy) = y 2 z 2 − x4 + x(x3 + y 3 + z 3 ) ≥ 4xyz yz √ (z 2 + xy)(x2 + xy) = z 2 x2 − y 4 + y(x3 + y 3 + z 3 ) ≥ 4xyz zx Adding the three. 15} to appear on the blackboard. 6 8. We have that X ai aj = 1≤i<j≤4 X ai aj + a3 a4 + (a3 + a4 )(a1 + a2 ) ≤ 2 1≤i<j≤2 X ai aj + rs + (r + s)(a1 + a2 ) 1≤i<j≤2 Hence. Without loss of generality. y 2 = zx. 15} cannot appear on the board. Find all triples (x. which shows that {2. 5 . f 2 (x)+8f . Plugging qx = yq q  in x = y = z into the first equation. 4. But. c} = {f2014 (x) + 4. 4. 6 . Let P (x) = 3x2 +18x+26 x3 +9x2 +24x+18 and define fn (x) by the following recurrence relation: f0 (x) = x − 4 and for n ≥ 1. 15}. the coded sum of {1. 7.Determine whether it is possible for the set of numbers {2. and z 2 = xy. we get √ √ √ x2 (y 2 − x2 ) + y 2 (z 2 − y 2 ) + z 2 (x2 − z 2 ) + (x + y + z)(x3 + y 3 + z 3 + xyz) ≥ 4xyz( xy + yz + zx) Our system of equations is the equality case to this inequality. For the second operation. let a3 and a4 be replaced by r and s. 7.or = z. we get that the only triplet 4 1007 4 1007 4 1007 is (x. We assert that the coded sum is nondecreasing. z) = . P Solution. y. 8}. The first operation clearly increases the coded sum because the terms simply increase. First consider the set of AM-GM results: √ x2 + yz ≥ 2x yz √ y 2 + zx ≥ 2y zx √ z 2 + xy ≥ 2z xy Multiplying the pairwise inequalities. + 4} satisfies a + b + c = abc 2014 (x)+17 f2015 (x) 2014 for all real x. i<j ai aj . 6 . which occurs when x2 = yz. 167. we assert that the coded sum increases. Define the coded sum to be. y. 3. the coded sum is nondecreasing. 6.

we have tan φ + tan 2φ + tan 3φ = tan φ tan 2φ tan 3φ. Hence. tan 2 · 32014 θ. But. so we’re done.Solution. tan 3 · 32014 θ}. Hence. An inductive argument can be used to show that fn (θ) = tan 3n θ − 4 if n is even and fn (θ) = cot 3n θ − 4 if n is odd. 6 . the triplet reduces to {tan 32014 θ. by identity. a + b + c = abc. Observe that P (x) = 3 x+3 1 (x+3)3 3 (x+3)2 − 1− which leads us to the identity P (tan θ−3) = cot 3θ and f0 (θ) = tan θ−4.